Hubungan Antara Pes Planus Dengan Keseimbangan Dinamis Pada Murid MI Nurul Karim Colomadu - Agus Setyo Nugroho; Fadhila Firma Nurulita (Poltekkes Kemenkes Surakarta, 2019)
Background: The ability to balance children at the age of development is very important to be reviewed, both in terms of balance sitting, standing, and walking. One of the factors that can cause balance disorders in children is musculoskeletal disorders in the form of deformity of the soles of the feet. The shape of the human foot is divided into three types, namely normal foot, pes planus and cavus foot according to the arcus structure or arches on the soles of the feet. Normally the arch is formed from the first 5 years with a 2-6 year age range. The critical period for arch formation is the age of 6 years (Campbell, 2012). In the early age of school there were 28% - 35% of children experiencing deformity of pes planus, 80% of which were categorized as